A proposal for a new universal development commitment - Jonathan Glennie; Nilima Gulrajani; Andrew Sumner; Myles A. Wickstead (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
Most Organization for Economic Co-operation and Development countries have accepted, in principle at least, the 50-year-old commitment of contributing 0.7 per cent of gross national income to supporting the development of countries in the Global South. But what if all countries made a universal development commitment, meaning a scaled contribution? We propose a new universal and scaled financial commitment to development, informed by but not necessarily identical to official development assistance. This paper: (i) sets out how a new era is emerging of fewer very poor countries and higher global ambitions-for example, to end poverty; (ii) proposes a new way to raise and govern international public funds; (iii) discusses the possible size and use of contributions, and the evolution in global governance and democracy that a new deal would entail. We conclude with a set of questions that the proposal raises.
Keywords: I30; F35; 330; Global; Global; Soziale Ungleichheit; Social inequality